Trends in development and quality assessment of pharmaceutical formulations - F2α analogues in the glaucoma treatment - Asendrych-Wicik, Katarzyna; Zarczuk, Jakub; Walaszek, Katarzyna; Ciach, Tomasz; Markowicz-Piasecka, Magdalena (European journal of pharmaceutical sciences, 2023)
The ocular delivery route presents a number of challenges in terms of drug administration and bioavailability. The low bioavailability following topical ophthalmic administration shows that there is a clear need for in-depth research aimed at finding both more efficacious molecules and formulations precisely targeted at the site of action. Continuous technological development will eventually result in improved bioavailability, lower dosages, reduced toxicity, fewer adverse effects, and thus better patient compliance and treatment efficacy. Technological development, as well as increasingly stringent quality requirements, help stimulate analytical progress. This is also clearly evident in the case of medicinal products used in the treatment of glaucoma, which are the subject of this review. Impurity profiling of PGF2α analogues, either in the pure substance or in the finished formulation, is a crucial step in assessing their quality. The development of specific, accurate and precise stability-indicating analytical methods for determining the content and related substances seems to be an important issue in relation to this tasks. A total of 27 official and in-house analytical methods are presented that are used for the analysis of latanoprost, travoprost and bimatoprost. The conditions for chromatographic separation with UV or MS/MS detection and the available results obtained during method validation are described. In addition, several aspects are discussed, with particular emphasis on the instability of the analogues in aqueous solution and the phenomenon of isomerism, which affects a potentially large number of degradation products. [Display omitted]